STUDY OF THE EFFECT OF STRUCTURE ON OCTANOL-WATER DISTRIBUTION OF 6-HYDROXYPYRIMIDINE-4-(3H)-ONES DERIVATIVES - A. E. Potapova; A. A. Teslev (Разработка и регистрация лекарственных средств)
The results of an experimental study of the effect of structure of substituting groups and pH value on the partition coefficients in biphasic systems of n-octanol and water for a number of 2,5-substituted 6-hydroxypyrimidine-4-(3H)-ones are presented.